Effect of Ascorbic Acid Concentration on Cu2O Production for Photoelectrochemical Water Splitting on Photocathode Thin Films - Kharisma Luthfiaratri Rahayu; Abdul Haris; Gunawan Gunawan (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Hydrogen energy has great potential as a renewable energy source. Electrochemical water-splitting can be employed to obtain hydrogen by converting solar energy into hydrogen. In this study, Cu2O thin film electrodes have been successfully synthesized using ascorbic acid using the spin coating method. This study aimed to determine the effect of ascorbic acid in manufacturing Cu2O semiconductors as photocathodes and their activity for electrochemical water-splitting. The results indicated that ascorbate affected the photon current and onset potential of the Cu2O semiconductor. The synthesis results found that Cu2O at C1 (lower concentration than Cu2+) yielded 95.69%, and the yield for Cu2O at C2 (concentration equal to Cu2+) was 96.2%. The yield for Cu2O at C3 (concentration greater than Cu2+) was 99.82%. The photon currents generated by adding 3%, 6%, and 9% ascorbate solution were 1.18, 1.69, and 1.78 mA/cm2, respectively, at 0.3 V vs. RHE (Reversible Hydrogen Electrode). X-ray diffraction analysis revealed that the sample consisted of Cu2O C3 with an average grain size of 17.55 nm. Meanwhile, Cu2O C1 and Cu2O C2 had average grain sizes of 38.99 nm and 36.42 nm, respectively. SEM analysis showed the presence of Cu2O with a cuboid and flower-like morphology. EDX analysis showed that the samples contained elements of Cu: O, 73.97%: 26.03%; 79.89%: 20.11% and 98.43%: 1.57% respectively.